Intradural migration of fusion cage in an isthmic listhesis patient treated with transforaminal lumbar interbody fusion (TLIF): A case report - Kızılay, Zahir; Yay, Murat Özcan; Kara, Ahmet Kürşat; Aydın, Varol (Journal of Surgery and Medicine, 2022)
Lumbar listhesis, is defined as a disorder that causes a vertebral body to slip over the one below it. Several surgical decompression and augmented fusion techniques are available for treatment. Transforaminal lumbar interbody fusion (TLIF) is a commonly used surgical technique for degenerative lumbar spondylolisthesis in cases in which conservative care fails to achieve satisfactory spinal fusion. Although TLIF is widely accepted because it is easy to perform and is very safe, cage migration is an important complication, and posterior migration is a serious one. Cage migration can be classified as posterior, anterior, or sagittal forms according to migration direction. An increasing number of the surgeons have encountered cage migration; however, consensus on its cause is lacking. In this report, a case of intradural cage migration with left leg pain is presented, and this complication is discussed in light of related studies.